2020
DOI: 10.1007/s10902-020-00311-y
|View full text |Cite
|
Sign up to set email alerts
|

Personal Life Satisfaction as a Measure of Societal Happiness is an Individualistic Presumption: Evidence from Fifty Countries

Abstract: Numerous studies document that societal happiness is correlated with individualism, but the nature of this phenomenon remains understudied. In the current paper, we address this gap and test the reasoning that individualism correlates with societal happiness because the most common measure of societal happiness (i.e., country-level aggregates of personal life satisfaction) is individualism-themed. With the data collected from 13,009 participants across fifty countries, we compare associations of four types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 39 publications
4
53
1
6
Order By: Relevance
“…However, our results are in line with those obtained by Krys et al (2020) , where the scores of the Romanian sample were exceeded only by four of the 50 cultures included in the study. One explanation for these striking results could be that in both our sample, and the sample included in the Krys et al (2020) study, were composed of university students, whereas the national samples include participants of all ages. Recent research by Lawrie et al (2020) showed a negative relationship between age and life satisfaction in Romania.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our results are in line with those obtained by Krys et al (2020) , where the scores of the Romanian sample were exceeded only by four of the 50 cultures included in the study. One explanation for these striking results could be that in both our sample, and the sample included in the Krys et al (2020) study, were composed of university students, whereas the national samples include participants of all ages. Recent research by Lawrie et al (2020) showed a negative relationship between age and life satisfaction in Romania.…”
Section: Discussionsupporting
confidence: 92%
“…This was surprising given that Romania typically has some of the lowest subjective well-being scores on international surveys [e.g., Eurofound (2013) reported that Romania lies second from the bottom out of 27 EU countries on overall well-being]. However, our results are in line with those obtained by Krys et al (2020) , where the scores of the Romanian sample were exceeded only by four of the 50 cultures included in the study. One explanation for these striking results could be that in both our sample, and the sample included in the Krys et al (2020) study, were composed of university students, whereas the national samples include participants of all ages.…”
Section: Discussionsupporting
confidence: 56%
“…Por otro lado, la conducta humana también obedece a una parte social (APA, 2010). En este tenor, desde la perspectiva cultural, que posee un lugar central en esta investigación, se resalta que la cultura interviene en la comprensión de las variables independientes ya mencionadas (Krys et al, 2021;Salzman, 2018), y en cómo éstas son percibidas por personas que forman parte de diferentes grupos sociales, como es el caso del entorno intercultural. Asimismo, la cultura juega un papel relevante para la comprensión del optimismo financiero (White et al, 2021).…”
Section: Discussionunclassified
“…Dentro del entorno Latinoamericano, Núñez et al (2020) encontraron una asociación significativa y positiva en estudiantes de México y Bolivia; sin embargo, a pesar de este tipo de estudios, existe poca investigación enfocada hacía un contexto intercultural, específicamente orientado a estudiantes de pueblos originarios. Esto se hace más pertinente al considerar que la cultura tiene una relación importante respecto a la interpretación de la satisfacción con la vida (Krys et al, 2021) y la autoestima (Salzman, 2018).…”
Section: Otros Antecedentesunclassified
“…The current study was part of a larger cross-cultural investigation, which was approved by research ethics committees, of the cultural antecedents of happiness, family well-being, and the valuation of different types of well-being (see also Krys et al, 2020). Measures of frequency of experience and frequency of expression of 30 different emotions were included to study a society's 'emotional environment' -we used these data to investigate our current research questions.…”
Section: Methodsmentioning
confidence: 99%